Double-Faced Immunological Effects of CDK4/6 Inhibitors on Cancer Treatment: Challenges and Perspectives - Yongqin Liu; Yiying Deng; Chang Yang; Hua Naranmandura (Bioengineering)
Cyclin-dependent kinases (CDKs) are generally involved in the progression of cell cycle and cell division in normal cells, while abnormal activations of CDKs are deemed to be a driving force for accelerating cell proliferation and tumorigenesis. Therefore, CDKs have become ideal therapeutic targets for cancer treatment. The U.S FDA has approved three CDK4/6 inhibitors (CDK4/6is) for the treatment of patients with hormone receptor-positive (HR+) or human epidermal growth factor receptor 2-negative (HER2−) advanced or metastatic breast cancer, and these drugs showed impressive results in clinics. Besides cell-cycle arrest, there is growing evidence that CDK4/6is exert paradoxical roles on cancer treatment by altering the immune system. Indeed, clinical data showed that CDK4/6is could change the immune system to exert antitumor effects, while these changes also caused tumor resistance to CDK4/6i. However, the molecular mechanism for the regulation of the immune system by CDK4/6is is unclear. In this review, we comprehensively discuss the paradoxical immunological effects of CDK4/6is in cancer treatment, elucidating their anticancer mechanisms through immunomodulatory activity and induction of acquired drug resistance by dysregulating the immune microenvironment. More importantly, we suggest a few strategies including combining CDK4/6is with immunotherapy to overcome drug resistance.